IMAGE PROCESSING APPARATUS AND CONTROL METHOD THEREOF - HIGASHIYAMA TERUYUKI (2015)
PROBLEM TO BE SOLVED: To reduce a possibility to exert an influence unallowable for a user on images to be combined even in the case where a changed undesirable for the user occurs in the middle of multiple times of imaging.SOLUTION: An image processing apparatus includes: detection means for detecting a camera shake of an imaging apparatus, a variation of a subject luminance or a variation of a subject color temperature; imaging control means which performs control in such a manner that the imaging apparatus performs imaging multiple times in accordance with one imaging instruction; combination means for combining a plurality of images which are captured in accordance with the one imaging instruction; and control means by which, in the case where the predetermined camera shake, the predetermined subject luminance variation or the predetermined subject color temperature variation is detected, on the basis of a result of the detection in the detection means, a synthetic image is generated by combining a plurality of images which are captured before the detection, without including images which are captured after the detection. 【課題】 複数回の撮影の途中で、ユーザにとって望ましくない変化が起きた場合にも、合成される画像にユーザが許容できないような影響を及ぼす可能性を低減させる。【解決手段】 撮像装置のブレまたは被写体輝度の変動または被写体色温度の変動を検知する検知手段と、１回の撮影指示に応じて前記撮像装置が複数回の撮影を行うように制御する撮影制御手段と、前記１回の撮影指示に応じて撮影された複数の画像を合成する合成手段と、前記検知手段での検知結果に基づいて、所定のブレまたは所定の被写体輝度の変動または所定の被写体色温度の変動を検出した場合に、前記検出の後に撮影された画像を含めずに、前記検出の前に撮影された複数の画像を合成した合成画像を生成するように前記合成手段を制御する制御手段と、を有することを特徴とする画像処理装置。【選択図】 図３